Diseño de Estrategias Pedagógicas Para El Manejo del Espacio Coreográfico en Los Estudiantes de Segundo B Colegio Colombo Florida Bilingüe (2017)
The present investigation relates the systematization process of the problems found in grade 2 B, from the Colombo Florida bilingual school management of the choreographic space, where They do some diagnostic tests, to reveal the problem, work is done pedagogical and didactic in the dance class, it was evident that the students did not manage the individual – collective space, recognizing that space is part of intelligence and evolutionary development in children, we work through the sequence of movement and play.